PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. PLN (PERSERO) (Studi Pada Unit Pelaksana Pelayanan Pelanggan Sumbawa Besar) - Resa Aprianti; Dewi Maharani; Nyoman Sutama (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of service quality, including reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), and tangible (X5) on customer satisfaction using the services of PT. PLN (Persero) Customer Service Implementation Unit (UP3) Sumbawa Besar. This research is associative research. The type of data used is quantitative data obtained from primary sources. The population in this study were all customers of PT. PLN (Persero) Customer Service Implementation Unit (UP3) Sumbawa Besar, amounting to 926,350 people, while determining the number of samples using the Slovin formula. Based on the calculation results obtained a sample of 100 people who were selected randomly. Data was collected through a questionnaire and analyzed using multiple linear regression analysis techniques, t and F tests, and the coefficient of determination (R2) test. The results showed that the quality of service consisting of reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), and tangibles (X5) had a positive and significant effect on customer satisfaction using the services of PT. PLN (Persero) Customer Service Implementation Unit (UP3) Sumbawa Besar, either partially or simultaneously. The degree of influence of service quality consisting of reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), and tangibles (X5) on customer satisfaction using the services of PT. PLN (Persero) Customer Service Implementation Unit (UP3) Sumbawa Besar is 61.2%, while the rest is influenced by other variables outside this research model.